2021
DOI: 10.2147/ijn.s301552
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Functional PLGA Nanoparticles Co-Loaded with Indocyanine Green and Resiquimod for Prostate Cancer Treatment

Abstract: Purpose With the advance of screening techniques, there is a growing number of low-risk or intermediate-risk prostate cancer (PCa) cases, remaining a serious threat to men’s health. To obtain better efficacy, a growing interest has been attracted to develop such emerging treatments as immunotherapy and focal therapy. However, few studies offer guidance on whether and how to combine these modalities against PCa. This study was designed to develop dual-functional nanoparticles (NPs) which combined p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Then, the LE of ICG in ICG@PSMA NPs was calculated to be 6.2%, which is comparable to many other different types of polymer encapsulated ICG nanoparticles, such as H-PMOF (17.4%), 27 CMCh-BAPE-RGD@ICG Nanoparticles (7.5%), 28 PLGA-ICG-R848 NPs ((0.82 ± 0.03)%). 49 …”
Section: Resultsmentioning
confidence: 99%
“…Then, the LE of ICG in ICG@PSMA NPs was calculated to be 6.2%, which is comparable to many other different types of polymer encapsulated ICG nanoparticles, such as H-PMOF (17.4%), 27 CMCh-BAPE-RGD@ICG Nanoparticles (7.5%), 28 PLGA-ICG-R848 NPs ((0.82 ± 0.03)%). 49 …”
Section: Resultsmentioning
confidence: 99%
“…In this case, the NK cells become irreplaceable as they can recognize tumor cells and mount a rapid immune response without antibodies or MHC [38]. Wenfeng Lin et al reported that PLGA-ICG-R848 after laser irradiation can stimulate the increased number of NK cells and generate an anti-tumor immune response via secretion of chemokines and cytokines, but HNP as a PTT material on the activation of NK cells has not yet been reported [39,40]. In terms of mechanism, we also explored the effect of HNP on NK cells under 808 nm laser irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…111 The systemic toxicity with these two main metabolites is minimal because they are efficiently cleared from the body. 112…”
Section: Recent Applications Of Ptx Nanomedicine For the Treatment Of...mentioning
confidence: 99%